CREATION OF ECONOMICAL RECYCLE FLOWER POTS IN LENGKONG KULON VILLAGE - Iqbal Maimun Umar; Joni Nur Budi Kawulur; Kathleen Manilova; Cristian Arthur; Silvia Theresia Onggo; Wilhelmus William Syarifudin (Jurnal Sinergitas PKM & CSR, 2023)
Packaging waste sometimes becomes a collective problem if it is not handled quickly, especially made from plastic which is difficult to decompose. Plastic waste can only decompose in hundreds of years, depending on the type of plastic. Various methods have been used to handle plastic waste, some are thrown in random places such as rivers, ditches which can block water channels when it rains, buried in the ground where it is difficult to decompose, or burned which produces pungent smoke. In the Internal UMN PKM we raised the theme of Creating Economical Water Gallon Recycling Flower Pots in Lengkong Kulon Village. The participants were mothers and young women. Location of UMN Lengkong Kulon Serpong village. The methods include licensing, location survey, outreach, preparation of equipment and materials, coordination of the PKM team, involvement of students and their job desk. The workshop trainer technique provides direction and supervision. direct practice and followed by participants one by one. The target for the output of the pot works is from gallon material until it is ready to be used and to decorate the home yard. The stages are from forming the pot, basic coloring to painting the pot motif. Another aim is for participants to be able to create independently and pass on their skills to the surrounding residents. It is hoped that they will be able to support a beautiful, clean, neat, sustainable village layout so as to build a Village Appearance Branding through the creative work of flower pots from gallon recyle. Other outputs are online mass media publications, national journals, making documentary videos and uploading them to YouTube and registering with IPR.